Rationality and Ascriptive Science - Itzhak Gilboa (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
This paper suggests definitions for two closely related terms which are (or could be) used in the social sciences. First, "rationality" is defined as a behavior which will not be altered as a result of awareness to its analysis. Next, an "ascriptive theory" is defined to be a descriptive theory which may become common knowledge among its subjects, yet remain valid. The relation between these concepts–as well as between them and others–is studied, and an "impossibility theorem," due to Dostoyevsky, is discussed.
Keywords: 330